Serum triiodothyronine determination in clinical use. Issue 7 (July 1976) - Stafford, J E; Lees, S; Watson, D
Abstract : Two radioimmunassays for the determination of serum triiodothyronine (T3) were developed. The assay of T3 in unextracted serum had several advantages over the assay on extracted serum and was chosen for the routine determination of T3 in serum from 117 patients requiring assessment of their thyroid status. In 53 subjects considered retrospectively not to have thyroid dysfunction nor to have been on steroid contraceptives or therapy, the pooled mean serum T3 concentration was 1-92 (actual range 0-88-2-62) nmol/l. A significant inverse relationship was observed between the serum T3 level and the age of the subject. Serum total T3 levels discriminate clearly between hypo-, eu- and hyperthyroid patients and provide a rather more sensitive index of hyperthyroid function than total serum T4. In the face of normal serum T4 the T3 level was depressed in five patients with marked hypoproteinaemia and elevated in two patients taking heroin.